PENGARUH KOMPETENSI SDM DAN DIGITAL MARKETINGTERHADAP KINERJA UMKM DI KABUPATEN TOBA - Merry Moy Mita; Supriadi Siagian (SUAN PUBLISHER, 2026)
This study is designed to examine the effects of human resource (HR) competence and digital marketing on the performance of micro, small, and medium enterprises (MSMEs) in Toba Regency, North Sumatra, Indonesia. The study responds to the need for locally embedded MSMEs to convert regional economic opportunities into sustainable business performance through stronger internal capabilities and more effective use of digital channels. The conceptual model integrates the Resource-Based View and Dynamic Capabilities Theory, positioning HR competence as a strategic internal resource and digital marketing as an adaptive capability through which MSMEs can reach, understand, and respond to changing markets. A quantitative correlational-descriptive design with an explanatory orientation is proposed. Primary data will be collected using a five-point Likert questionnaire from 100–150 MSME owners or managers whose firms have operated for at least one year and already use social media or other digital platforms for marketing. Multiple linear regression will be conducted after assessing instrument validity and reliability and examining residual normality, multicollinearity, and heteroscedasticity. Partial and simultaneous hypotheses will be evaluated using t-tests, the F-test, and the coefficient of determination at the 5% significance level. As the primary dataset was not provided at the manuscript-development stage, empirical coefficients, significance values, and statistical conclusions are intentionally left unreported to preserve research integrity. The manuscript therefore offers a complete pre-results framework that can be finalized immediately after the actual survey data are analyzed.